Undergraduate medical Students’ perspective to Community?based Education and Services (COBES) Attachment in the Rural Primary Health Care Settings in Namibia - Barongo, Longin R.; Lukolo, Linda N. (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2019)
ObjectiveTo examine the students’ perspective on whether Community Based Education and Services (COBES) practices in the rural settings was in line with school learning objectives, be able to identify deficiencies in the design and in the implementation of COBES program.MethodsA total of 100 students were analyzed, 30 out of 55(55%) from the year 2013, 35 out of 65 (54%) from year 2014 and 35 out of 70 (51%) from year 2015. These students were randomly selected from the cohort of students in their respective year of study. In their log books students were required to respond to each of the objectives given, the importance of each objectives in relation to the situation they saw in the rural primary health settings and identify deficiencies in the design and implementation of the program.ResultsAll students (100%), acknowledged improved practical skills including history taking, physical examination and performance of outpatient procedures as outlined in their log-books under supervision. More than 2/3 of the students appreciated how the primary health care facilities were organized in a multidisciplinary way and well-coordinated on day to day basis. Among the many challenges identified include inadequate number of staff members, lack of technical and specialist support. About 50% of the students were able to associate poverty and type of diseases commonly found in those communities.ConclusionAll the three cohorts expressed that the rural replacement enhanced their learning and increased skills because they were exposed to a variety of medical problems hardly seen at the teaching hospital .About 2/3 of all students appreciated working in a multidisciplinary team that include all primary health care staff. To many students this rotation was an eye opener to the type of life in the rural settings. Some of those students were born and raised in towns.